Virtual Design and Construction (VDC) Framework: A Current Review, Update and Discussion - Del Savio, Alexandre Almeida (2022)
Compared with other industries, construction has maintained one of the lowest growth rates in productivity and innovation over the last decades. Moreover, low compliance with schedule targets has remained a common issue throughout projects. Therefore, although methodologies developed have benefited productivity in design, construction and operation, meeting client and project objectives becomes challenging without properly integrating organization, information, systems and processes. This perspective introduces the Virtual Design and Construction (VDC) framework. First, this paper studies and reviews VDC since its creation at the Center for Integrated Facility Engineering (CIFE) of Stanford University in 2001. After that, a comprehensive bibliographical review of the VDC framework is presented and updated with examples of its application in construction projects, delving into its elements: Client Objectives, Project Objectives, Production Objectives, Controllable Factors, Integrated Concurrent Engineering (ICE), Building Information Modeling (BIM) and Project Production Management (PPM). Finally, the main benefits and project outcomes when applying the VDC framework are presented and discussed, followed by the conclusions and recommendations for future research.